2017
DOI: 10.1590/1806-9282.63.09.793
|View full text |Cite
|
Sign up to set email alerts
|

Ischemic left ventricle systolic dysfunction: An evidence-based approach in diagnostic tools and therapeutics

Abstract: Summary Coronary artery disease (CAD) associated with left ventricular systolic dysfunction is a condition related to poor prognosis. There is a lack of robust evidence in many aspects related to this condition, from definition to treatment. Ischemic cardiomyopathy is a spectrum ranging from stunned myocardium associated with myocardial fibrosis to hibernating myocardium and repetitive episodes of ischemia. In clinical practice, relevance lies in identifying the myocardium that has the ability to recover its c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(18 citation statements)
references
References 47 publications
0
16
0
2
Order By: Relevance
“…Despite these serious clinical implications, IHF lacks a definite terminology [4]. Most IHF studies refer to the condition as ischemic left ventricle (LV) systolic dysfunction or ischemic cardiomyopathy [5][6][7]. Many other studies refer to IHF using its sequalae -ischemic heart disease (IHD) [3,8], acute coronary syndrome (ACS) [9,10], coronary heart disease (CHD) [11,12] or coronary atherosclerotic disease [13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Despite these serious clinical implications, IHF lacks a definite terminology [4]. Most IHF studies refer to the condition as ischemic left ventricle (LV) systolic dysfunction or ischemic cardiomyopathy [5][6][7]. Many other studies refer to IHF using its sequalae -ischemic heart disease (IHD) [3,8], acute coronary syndrome (ACS) [9,10], coronary heart disease (CHD) [11,12] or coronary atherosclerotic disease [13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…47 In concordance with the previous ndings, our results also validate the recapitulation of Hh signaling pathway in ischemic heart disease patients but more prominently in impaired (LVEF <45) group. 48 Considering that the Hh signaling pathway is essential for the formation of new coronary vessels, this nding signals an important adaptive mechanism in humans with LVSD. 49 KEGG pathway analysis also showed that pathways involved in the Metabolism of steroids (pathway proteins: albumin, oxysterol-binding protein-related protein 6, sterol regulatory element-binding protein 2), plasma lipoprotein remodelling (pathway proteins: albumin, apolipoprotein A-IV) and bile acid and bile salt metabolic pathways (pathway proteins: albumin, oxysterol-binding protein-related protein 6) were downregulated in impaired (LVEF <45) group as compared to the normal (LVEF $45) group.…”
Section: Discussionmentioning
confidence: 99%
“…PET has a reasonable sensitivity, but still limited specificity [18]. While the quality of the images is very good, still the technique is quite expensive [19]. Stress tests combined with nuclear techniques are novel tests which help find the specific coronary vessel responible for the damaged tissue.…”
Section: Myocardial Scintigraphymentioning
confidence: 99%